Editorial for the Special Issue on Meaningful Human Control and Autonomous Weapons Systems - Steven Umbrello (Information, 2022)
Global discussions on the legality and ethics of using Artificial intelligence (AI) technology in warfare, particularly the use of autonomous weapons (AWS), continue to be hotly debated [...]